The intersection between sex and drugs: a cross-sectional study among the spouses of injection drug users in Chennai, India - Anand Santhanam; Murugavel Kailapuri G; Vasudevan Canjeevaram K; Johnson Sethulakshmi C; Celentano David D; Srikrishnan Aylur K; Solomon Sunil S; Kumar M Suresh; Solomon Suniti; Mehta Shruti H (BMC, 2011)
Abstract Background It is estimated that there are up to 1.1 million injection drug users (IDUs) in India; the majority are likely married. We characterize HIV, hepatitis B (HBV) and hepatitis C (HCV) prevalence and the risk environment of a sample of spouses of IDUs. Methods A cohort of 1158 IDUs (99% male) was recruited in Chennai, India from 2005-06. A convenience sample of 400 spouses of the male IDUs in this cohort was recruited in 2009. A risk assessment questionnaire was administered and a blood sample collected. Logistic regression was used to identify factors associated with prevalent HIV. Results Median age was 31 years; thirteen percent were widowed and 7% were not currently living with their spouse. Only 4 (1%) reported ever injecting drugs; Twenty-two percent and 25% reported ever using non-injection drugs and alcohol, respectively. The majority had one lifetime sexual partner and 37 (9%) reporting exchanging sex. Only 7% always used condoms with their regular partner. HIV, HBV and HCV prevalence were 2.5%, 3.8% and 0.5%, respectively; among spouses of HIV+ IDUs (n = 78), HIV prevalence was 10.3%. The strongest predictor of HIV was spousal HIV status (OR: 17.9; p < 0.001). Fifty-six percent of women had ever experienced intimate partner violence; Eight-six percent reported sexual violence. Conclusions Our finding of a 10-fold higher HIV prevalence among spouses of IDUs compared with general population women indicates their vulnerability; prevalence is likely to increase given the context of low condom use and frequent sexual violence. Prevention efforts directed at IDUs should also include programs for spouses.